2017
DOI: 10.1186/s12933-017-0514-x
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative increased risk of incident type 2 diabetes mellitus with increasing triglyceride glucose index in normal-weight people: The Rural Chinese Cohort Study

Abstract: BackgroundRisk of type 2 diabetes mellitus (T2DM) is increased in metabolically obese but normal-weight people. However, we have limited knowledge of how to prevent T2DM in normal-weight people. We aimed to evaluate the association between triglyceride glucose (TyG) index and incident T2DM among normal-weight people in rural China.MethodsWe included data from 5706 people with normal body mass index (BMI) (18.5–23.9 kg/m2) without baseline T2DM in a rural Chinese cohort followed for a median of 6.0 years. A Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
170
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 208 publications
(199 citation statements)
references
References 53 publications
13
170
0
1
Order By: Relevance
“…compared the TyG index with the euglycemic‐hyperinsulinemic clamp test, and suggested that TyG could be useful for the identification of individuals with decreased insulin sensitivity in 2010 . A series of cohort and cross‐sectional studies confirmed a strong correlation between the TyG index and IR, type 2 diabetes mellitus, MetS, hypertension, cardiovascular events and fatty liver both in China and elsewhere. Published studies have shown that the TyG index is helpful for the prediction and early identification of individuals at high risk of cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…compared the TyG index with the euglycemic‐hyperinsulinemic clamp test, and suggested that TyG could be useful for the identification of individuals with decreased insulin sensitivity in 2010 . A series of cohort and cross‐sectional studies confirmed a strong correlation between the TyG index and IR, type 2 diabetes mellitus, MetS, hypertension, cardiovascular events and fatty liver both in China and elsewhere. Published studies have shown that the TyG index is helpful for the prediction and early identification of individuals at high risk of cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Trained staff collected details of demographic characteristics by face‐to‐face interview with a standard questionnaire. The variables and questionnaire were described previously . Smokers were defined as currently smoking and/or having smoked 100 or more cigarettes during their lifetime .…”
Section: Methodsmentioning
confidence: 99%
“…20 Alcohol use was defined as drinking alcohol more than 12 times during the past year. 18 Physical activity level was assessed using the International Physical Activity Questionnaire (IPAQ) scoring protocol. 21 All participants were asked to wear light clothing and no shoes for physical measurements.…”
Section: Measurement and Data Collection At Baselinementioning
confidence: 99%